Стратегічні можливості розвитку студентських громадських організацій - Кулініч, Т. В.; Сороката, А. В.; Kulinich, T.; Sorokata, A. (Видавництво Львівської політехніки, 2019)
Показано результати дослідження стратегічних можливостей і варіантів формування дієвих стратегічних ходів у розвитку молодіжних громадських організацій (МГО), зокрема студентських (СГО). Реальні стратегічні альтернативи відображено на прикладі декількох СГО, що конкурують у Західному регіоні України: “BEST Lviv”, “AISEC”, “AEGEE” та “ФРІ”. Проведена за рядом методів стратегічна діагностика дала змогу розробити рекомендації з підвищення конкурентоспроможності “BEST Lviv”. Результати дослідження також допомогли запропоновувати альтернативні стратегічні заходи для розвитку названої СГО, які ґрунтуються на варіантах саморозвитку студентів (її активних і пасивних учасників) і водночас створюють основу для підвищення ефективності діяльності зазначеної організації.

The object of analysis is strategic management of Youth Non-governmental Organization (YNGO) activities (in particular, Student NGO). At this publication we have purpose to show the results of a study of strategic opportunities and options for formation of effective strategic moves in the development of SNGOs. It is important to display different real strategic alternatives at the example of several SNGOs which represent the Western region of Ukraine. The results of the research are following. YNGOs and their subspecies of SNGOs differ from other organizations primarily in the fact that during their management the main emphasis is transferred from financial resources to human resources, and expenses are measured not by money, but by the time and efforts of volunteers. The strategic opportunities for development of domestic SNGOs in this article were examined at the example of the “BEST Lviv” YNGO, the main features of which are: non-profit, non-political, non-religious and non-governmental nature; existence at a technical university (namely, Lviv Polytechnic National University); membership in it is limited only to students of the specified university. In addition to the study of the YNGO “BEST Lviv”, there was also identified the main competitors of the organization (YNGO “AISEC”, “AEGEE” and “FRI”) at the own established criteria and their detailed study was realized. The implementation of strategic diagnostics was accompanied by SWOT analysis. The following strengths of the YNGO “BEST Lviv” were identified: highly qualified members, high-quality organization of activities according to the VMOST system, well-structured system, well-thought-out social microclimate, spelled out norms and available human resources. The weakness is the lack of public support for the organization. As a result, there were developed recommendations to improve the competitiveness of the analyzed YNGO: achieving financial stability by attracting new partners; strengthening ties with existing ones and receiving grants; the use of available funds for renting a new office, improving the quality of project organization and financial support for recruitment; improving the system of motivation and mentoring; conducting in-depth analysis of the supply and demand market. The results of the study also permit us to propose alternative strategic measures for the development of YNGO “BEST Lviv”, based on self-development options for students (active and passive participants), which could increase the effectiveness of this YNGO: support for participation in external trainings, development projects, internal international events of “BEST”; career support abroad; assistance in post-project self-realization of personality; development assistance through competitions; providing useful content-filling of pages of YNGO in social networks. The practical significance of the paper lies in the invention of new opportunities for effective strategic management of real YNGOs.
Strategic opportunities for development of student social organizations
Keywords: стратегія; можливості; розвиток; молодіжна громадська організація (МГО); студенти; учасники; strategy; opportunities; development; youth non-governmental organization (YNGO); students; participants; 339.658